Integrated analysis of the lncRNA-miRNA-mRNA network based on competing endogenous RNA in atrial fibrillation - Wang, Manman; An, Guoying; Wang, Benxuan; Chen, Yuanyuan; Liu, Genli; Wang, Xin; Liu, Shuai; Zhang, Daozou; Sun, Dandan; Zhang, Yanyan; Shen, Tong; Li, Xiangting (Frontiers in Cardiovascular Medicine, 2023)
Objective Long non-coding RNAs (lncRNAs) play pivotal roles in the transcriptional regulation of atrial fibrillation (AF) by acting as competing endogenous RNAs (ceRNAs). In the present study, the expression levels of lncRNAs of sinus rhythm (SR) patients and AF patients were investigated with transcriptomics technology, and the lncRNA-miRNA-mRNA network based on the ceRNA theory in AF was elaborated. Methods Left atrial appendage (LAA) tissues were obtained from patients with valvular heart disease during cardiac surgery, and they were divided into SR and AF groups. The expression characterizations of differentially expressed (DE) lncRNAs in the two groups were revealed by high-throughput sequencing methods. Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analyses were performed, and the lncRNA-miRNA-mRNA-mediated ceRNA network was constructed. Results A total of differentially expressed 82 lncRNAs, 18 miRNAs, and 495 mRNAs in human atrial appendage tissues were targeted. Compared to SR patients, the following changes were found in AF patients: 32 upregulated and 50 downregulated lncRNAs; 7 upregulated and 11 downregulated miRNAs; and 408 upregulated and 87 downregulated mRNAs. A lncRNA-miRNA-mRNA network was constructed, which included 44 lncRNAs, 18 miRNAs, and 347 mRNAs. qRT-PCR was performed to verify these findings. GO and KEGG analyses suggested that inflammatory response, chemokine signaling pathway, and other biological processes play important roles in the pathogenesis of AF. Network analysis based on the ceRNA theory identified that lncRNA XR_001750763.2 and Toll-like receptor 2 (TLR2) compete for binding to miR-302b-3p. In AF patients, lncRNA XR_001750763.2 and TLR2 were upregulated, and miR-302b-3p was downregulated. Conclusion We identified a lncRNA XR_001750763.2/miR-302b-3p/TLR2 network based on the ceRNA theory in AF. The present study shed light on the physiological functions of lncRNAs and provided information for exploring potential treatments for AF.